Activation of Inward Rectifier K+ Channel 2.1 by PDGF-BB in Rat Vascular Smooth Muscle Cells through Protein Kinase A. (2nd May 2020) - Tang, Chengchun; Wang, Dong; Luo, Erfei; Yan, Gaoliang; Liu, Bo; Hou, Jiantong; Qiao, Yong
Abstract : Platelet-derived growth factor-BB (PDGF-BB) can induce the proliferation, migration, and phenotypic modulation of vascular smooth muscle cells (VSMCs). We used patch clamp methods to study the effects of PDGF-BB on inward rectifier K + channel 2.1 (Kir2.1) channels in rat thoracic aorta VSMCs (RASMCs). PDGF-BB (25 ng/mL) increased Kir2.x currents (− 11.81 ± 2.47  pA/pF, P < 0.05 vs. CON, n = 10 ). Ba 2+ (50  μ M) decreased Kir2.x currents (− 2.13 ± 0.23  pA/pF, P < 0.05 vs. CON, n = 10 ), which were promoted by PDGF-BB (− 6.98 ± 1.03  pA/pF). PDGF-BB specifically activates Kir2.1 but not Kir2.2 and Kir2.3 channels in HEK-293 cells. The PDGF-BB-induced stimulation of Kir2.1 currents was blocked by the PDGF-BB receptor β (PDGF-BBR β ) inhibitor AG1295 and was not affected by the PDGF-BBR α inhibitor AG1296. The PDGF-BB-induced stimulation of Kir2.1 currents was blocked by the protein kinase A inhibitor Rp-8-CPT-cAMPs; however, the antagonist of protein kinase B (GSK690693) had marginal effects on current activity. The PDGF-BB-induced stimulation of Kir2.1 currents was enhanced by forskolin, an adenylyl cyclase (AC) activator, and was blocked by the AC inhibitor SQ22536. We conclude that PDGF-BB increases Kir2.1 currents via PDGF-BBR β through activation of cAMP-PKA signaling in RASMCs.